The Impact of Firm Size on Firm Value: A Mediation Study of Profitability and Capital Structure - Achmad Naufal Afifuddin; Taufik Akbar (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to examine the effect of Company Size on Firm Value and analyze the mediating role of Profitability and Capital Structure in companies listed in the IDX30 index during the 2021–2023 period. The indicator variables used for Company Size are SIZE, Firm Value using Price to Book Value (PBV), Profitability using Return on Assets (ROA), and Capital Structure using the Debt to Equity Ratio (DER) as the measurement indicator. The method used is panel data regression and the Sobel test with a Random Effects Model approach. The results show that company size has no significant effect on profitability (ROA) or capital structure (DER). However, company size is proven to have a significant negative effect on firm value (PBV). On the other hand, profitability has a positive but insignificant effect on firm value, while capital structure shows a significant positive effect on firm value. The results of the mediation test also confirm that neither profitability nor capital structure successfully mediates the relationship between company size and firm value significantly.